POLA PEMBENTUKAN SIKAP HOMO-ECONOMICUS DAN HOMO-SOCIALICUS MELALUI PENGEMBANGAN TUJUAN PEMBELAJARAN (Suatu Model Inovatif Pengembangan Kurikulum Ekonomi) - Jun Surjanti, (Pendidikan Ekonomi, 2010)
The study is intended to  present a thought about the development of economic learning objectives for junior or senior high schools, that is, the developmental stage of homosocialiscus attitude for students as economic beings. That is why, the economic materials or lessons are based on character  development concerning social milieu. On senior high school level, learning economics is aimed to develop homoeconomicus attitude, that is, rational attitude as economic beings who are able to keep harmony of economic life and expand economic relation through international trade. General elaboration is aimed for the development of rational attitude in running economic activities by budgeting activities, reporting sequentially, and being accountable for financial accounts.